2015
DOI: 10.1007/s40195-015-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

Pitting Kinetics of 304 Stainless Steel Using ESPI Detection Technique

Abstract: The electronic speckle pattern interferometer was used to in situ monitor the pitting corrosion of 304 stainless steel at anodic polarization. The pitting current and pitting current density of a single pit were obtained. The pit growth was controlled by the corrosion products diffusion. The pit morphology was observed by a scanning electron microscope. The results showed that the pit was dish shaped, and the geometric parameters and pit growth time conformed to the function of Y = A ? B 1 t ? B 2 t 2 ? B 3 t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The improvement in the cyclic oxidation resistance of NiAl-30.9Cr-3Mo-0.1Dy alloy is due to the formation of continuous and compact Al 2 O 3 external layer [20]. Besides, as reported by Tian et al [21], the addition of Dy enhances the room-temperature and high-temperature compressive strength and room-temperature compressive ductility of Nb-Si-based alloys. However, the effect of Dy on the oxidation behavior of Nb-Si-based alloys has not been systematically explored.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The improvement in the cyclic oxidation resistance of NiAl-30.9Cr-3Mo-0.1Dy alloy is due to the formation of continuous and compact Al 2 O 3 external layer [20]. Besides, as reported by Tian et al [21], the addition of Dy enhances the room-temperature and high-temperature compressive strength and room-temperature compressive ductility of Nb-Si-based alloys. However, the effect of Dy on the oxidation behavior of Nb-Si-based alloys has not been systematically explored.…”
Section: Introductionmentioning
confidence: 64%
“…It is observed that Dy is mainly partitioned in silicides, especially in cNb 5 Si 3 . Tian et al [21] reported that the Dy addition remarkably refined the size of (Nb,Ti) 5 Si 3 phase in Nb-23Ti-10Ta-2Cr-18Si alloy (at.%), as rare earth element of Dy had a high surface activity and tended to reduce the surface tension of liquid Nb-Si melt as well as the nucleation energy during solidification. However, for the Nb-15Si-24Ti-4Cr-2Al-2Hf alloy, the Dy addition produces no obvious effect on the microstructure fineness.…”
Section: Methodsmentioning
confidence: 99%
“…However, metal ions diffused rapidly through the new corroded pores, which again decreased the local concentration of the salt solution and induced passivation at the edges. Therefore, during the film destruction and passivation at the pit edges, the pits continued to grow, causing the film to be destroyed repeatedly before finally forming corrosion pits with porous lacy covers [40][41][42][43].…”
Section: Corrosion Morphologymentioning
confidence: 99%
“…It is known that some corrosion products diffuse to the outside of pits during the growth of corrosion pits [10,11]. The hydrolysis of cations changes the corrosive environment of the passive film outside the pits [12].…”
Section: Introductionmentioning
confidence: 99%